(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Marzuki I, Ahmad R, Kamaruddin M, Asaf R, Armus R, Siswanty I. 2021. Performance of cultured marine sponges-symbiotic bacteria as a heavy metal bio-adsorption. Biodiversitas 22: 5536-5543. One source of heavy metal waste could be coming from industrial disposal. Contamination and accumulation of hazardous heavy metal waste are most likely to occur in water areas, It has become a global issue that urgently requires appropriate technology to address. Two marine sponge-symbiotic bacteria from the Spermonde islands, Indonesia, i.e., Bacillus cohnii strain DSM 6307 (BS) and Pseudomonas stutzeri RCH2 (PS), were used in this study. The purpose of this study is to investigate the mechanism of heavy metal bio-adsorption of two sponge symbiotic bacteria by contact technique and are assessed their activity, capacity, and efficiency of bio-adsorption against different heavy metals (Cr, Mn, Fe, Co, Cu, Zn, Ag, and Cd),. The bio-adsorption capacity was evaluated by Atomic Absorption Spectroscopy (AAS) after a predetermined contact time (4, 8, 12, and 16 days). The results demonstrated that two sponge symbiotic bacteria had bio-adsorption activities against eight different heavy metals. BS bacteria exhibited higher bio-adsorption capacity (Cr ? Zn ? Cu ? Fe ? Co ?Mn and Ag ? Cd) than that of PS bacteria (Zn ? Co ? Fe ? Mn ? Cu ? Cr and Cd ? Ag). The difference in the atomic number of heavy metals causes the characteristics of these metals to vary which affects the capacity and efficiency of bio-adsorption of sponge symbiotic bacteria to heavy metals.